Pengaruh Kecerdasan Emosional Terhadap Kedisiplinan Siswa - Gilang Maulana Jamaludin; Nurhayati Nurhayati (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2022)
This study aims to determine the effect of emotional intelligence on the discipline of SD Negeri Banjaran students. This study uses a quantitative approach with descriptive and correlation methods. The data collection tool is done by using a questionnaire to obtain information from respondents about the influence of emotional intelligence on student discipline. After the data is collected, it is analyzed using statistics and processed using the SPSS (Statistical Package for Social Sciences) version 21 program.Based on the calculation results, it turns out that there is a positive and significant influence. This is obtained from the calculation of the product moment correlation which is known that the value of the correlation coefficient of emotional intelligence is 0.932, which ranges from 0.800 - 1,000 indicating a very strong correlation and the direction of the relationship is positive. Then the correlation coefficient is significant, this is evidenced by the results of t count (26,476) which is greater than t table (2,629) which shows that there is an influence of emotional intelligence on the discipline of SD Negeri Banjaran students. The coefficient of determination in this study which shows the influence of emotional intelligence on student discipline is 86.9%. The remaining 13.1% is influenced by other factors such as example, advice, practice, and the environment.